Stromal Cell-Derived Factor-1 Enhances the Therapeutic Effects of Human Endometrial Regenerative Cells in a Mouse Sepsis Model - Wang Jin; Yiming Zhao; Yonghao Hu; Dingding Yu; Xiang Li; Yafei Qin; Dejun Kong; Hao Wang (Stem Cells International)
Endometrial regenerative cells (ERCs) are mesenchymal-like stromal cells obtained from human menstrual blood, whose positive therapeutic effects have been validated in several experimental models. Stromal cell-derived factor-1 (SDF-1), the ligand for CXCR4, plays an important role in the migration of mesenchymal stromal cells. The purpose of this study was to investigate the role of the SDF-1/CXCR4 pathway in the therapeutic effects of ERCs in a mouse sepsis model. Through preexperiment and confirmation, wild-type C57BL/6 mice were intraperitoneally injected with 10 mg/kg lipopolysaccharide (LPS). The therapeutic effects of ERCs with different pretreatments were evaluated by assessing sepsis-related symptoms, detecting tissue damage and measuring levels of inflammatory and oxidative stress-related factors. The in vitro experiments demonstrated that there was a much higher CXCR4 expression on ERCs when they were cocultured with SDF-1. The ex vivo experiment results showed that SDF-1 expression significantly increased in mouse tissues. Further experiments also confirmed that, compared with the unmodified ERC treatment group, SDF-1 pretreatment significantly enhanced the therapeutic effects of ERCs on alleviating sepsis symptoms, ameliorating pathological changes, reducing Bax level, and increasing Bcl-2 and PCNA expressions in mouse liver tissues. Furthermore, it was also found that SDF-1-pretreated ERCs contributed to reducing the levels of proinflammatory cytokines (TNF-α, IL-1β) and increasing the levels of anti-inflammatory factors (IL-4, IL10) in mouse serum, liver, and lung. Moreover, SDF-1-pretreated ERCs could also significantly decrease the levels of iNOS and MDA and increase the expression of Nrf2, HO-1, and SOD in liver tissues. Taken together, these results indicate that SDF-1 pretreatment plays a key role in improving the therapeutic effects of ERCs in alleviating sepsis-related symptoms, reducing tissue damage, regulating inflammatory imbalance, and relieving oxidative stress in a mouse sepsis model, which provides more possibilities for the clinical application of ERCs in sepsis and relevant diseases.